2017
DOI: 10.1128/mbio.00473-17
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Nucleotide Regulatory Motif within the AbcR Small RNAs of Brucella abortus Mediates Host-Pathogen Interactions

Abstract: In Brucella abortus, two small RNAs (sRNAs), AbcR1 and AbcR2, are responsible for regulating transcripts encoding ABC-type transport systems. AbcR1 and AbcR2 are required for Brucella virulence, as a double chromosomal deletion of both sRNAs results in attenuation in mice. Although these sRNAs are responsible for targeting transcripts for degradation, the mechanism utilized by the AbcR sRNAs to regulate mRNA in Brucella has not been described. Here, two motifs (M1 and M2) were identified in AbcR1 and AbcR2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…However, it stands to reason that one motif, M2, may be responsible for regulating targets that are directly or indirectly involved in pathogenesis. One of these M2‐regulated targets, BAB2_0612, was found to be involved in Brucella pathogenesis, strengthening this hypothesis (Sheehan and Caswell, ), and will be interesting to determine if any other M2 targets are linked to Brucella pathogenesis.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…However, it stands to reason that one motif, M2, may be responsible for regulating targets that are directly or indirectly involved in pathogenesis. One of these M2‐regulated targets, BAB2_0612, was found to be involved in Brucella pathogenesis, strengthening this hypothesis (Sheehan and Caswell, ), and will be interesting to determine if any other M2 targets are linked to Brucella pathogenesis.…”
Section: Introductionmentioning
confidence: 63%
“…Quantitative reverse‐transcriptase PCR with the B. abortus single and double abcR mutants found that the sRNAs are truly redundant, with the isogenic abcR mutants resulting in gene expression levels comparable to the wild‐type strain, and a double abcR mutant leading to over‐expression of target genes (Sheehan and Caswell, ). Furthermore, AbcR1 and AbcR2 both physically bind to the 5' UTR of one of the targets, BAB2_0879, confirming the redundant roles these sRNAs have in Brucella .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations